Prevalence of hyperuricemia in professional athletes and its role in the genesis of various pathological conditions and metabolic disturbances - M. S. Eliseev; I. Т. Vykhodets; I. V. Kruglova; M. N. Chikina; O. V. Zhelyabina; E. V. Ilyinykh; A. V. Zholinsky; S. V. Dodonov; A. M. Lila; Е. L. Nasonov (Современная ревматология, 2018)
In recent decades, the prevalence of hyperuricemia (HU) is increasing worldwide; the role of uric acid (UA) in the genesis of various metabolic disorders, cardiovascular diseases, and kidney disease is being discussed. There are very few investigations of the rate of HU and its role in the development of diseases in certain social groups, including in professional athletes.Objective: to estimate the prevalence of HU and its role in the genesis of various pathological conditions and metabolic disturbances in professional athletes.Patients and methods. A retrospective comparative one-stage study was conducted, for which 2148 athletes who met inclusion criteria were selected and examined in the Federal Research and Clinical Center for Sports Medicine and Rehabilitation, Federal Biomedical Agency, in 2015. A control group consisted of 99 ageand sex-matched healthy volunteers examined at the V.A. Nasonova Research Institute of Rheumatology in 2017. The analysis included a comparison of the rate of HU and other examined parameters in professional athletes and healthy volunteers. The examined parameters were separately compared in athletes with/without HU, followed by statistical processing of results.Results. HU was detected in 306 (14.2%) of the 2148 athletes, more often in men (n=253 (20%) than in women (n=53 (6%); (p<0.001). The rate of HU in the athletes was comparable with that in the healthy population (12.1%). The athletes with HU (n=306) compared with the other athletes (n=1842) had the following statistically higher indicators: the mean serum levels of creatinine, triglycerides, aspartate aminotransferase, alanine aminotransferase, gamma-glutamyltranspeptidase, creatinine phosphokinase, and myoglobin, glomerular filtration rate, and body mass index (BMI) (p<0.00001 for all cases).Conclusion. HU is detected quite often in professional athletes (14.2%), which is comparable with the indicators seen in healthy volunteers (12.1%). The high prevalence of HU and its association with indicators reflecting kidney function, lipid metabolic disturbances, and BMI necessitate further investigations aimed at searching the causes of HU and methods of its prevention and treatment in professional athletes.